A select library of the Nicene and Post-Nicene Fathers of the Christian church - Schaff, Philip; Wace, Henry; Athanasius Bishop of Alexandria (Edinburgh, Scotland T and T Clark, 1889)
Includes bibliographical references and indexes.
V.IV includes selected writings and letters of Athanasius, Bishop of Alexandria
Keywords: Fathers of the church -- Primitive and early church -- ca 30-600